The Mediating Effect of Job Satisfaction on the Relationship Between Leadership Styles and Employee Loyalty - Ramadhan Rafiq Ibrahim; Sri Gunani Partiwi (Jurnal Teknologi dan Manajemen Industri Terapan, 2026)
Employee loyalty is one of the key factors influencing the stability of organizational work systems. However, in practice, employee loyalty is often influenced by the leadership styles implemented within the organization. This study aims to analyze the influence of leadership styles (transformational, transactional, democratic, and autocratic) on employee loyalty by considering job satisfaction as a mediating variable. The research was conducted in the additive manufacturing industry in Batam, involving 163 respondents. Data were collected through questionnaires and analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM). The results indicate that transformational, transactional, and autocratic leadership styles have a positive and significant effect on job satisfaction, while democratic leadership does not. Furthermore, job satisfaction has a strong positive effect on employee loyalty and fully mediates the relationship between leadership styles and employee loyalty. None of the leadership styles directly influence employee loyalty. The study concludes that transactional leadership is the most effective style to boost job satisfaction and, consequently, employee loyalty in this industrial context.